The Majorat of Sartenejas in Colonial Venezuela 1740-1858 - Rangel, Egilda (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The process of incorporating land as private property began in the second half of the XVI century, in what nowadays is Venezuela, through process of favours.This process continued into the XVII century, based on litigation, purchase and sale of land. By the XVII century, this process is achieved through the system ofoccupation, which favoured the descendents of the irst conquistadors. Some time later, these descendents had achieved control over the economic and political life of Caracas. Some of these families decided to turn their properties into majorats. Through this institution, they were able to perpetuate their property within the family. In Venezuela, there were apparently three majorats, two of them were linked to the Bolivar family and the third one to the Cornieles family, in the city of Trujillo.However, we have conirmed the existence of more than twenty two majorats. One of them is the Majorat of Sartenejas, founded in 1740, by Lorenzo Antonio dePonte and Martinez de Villegas, based on law 33, of the Leyes de Toro. Three “noble” families with roots in Venezuela, the Mixares, Ponte and Tovar families were linked to the above-mentioned property and they were joined by marriage alliances to preserve their properties.